STRUCTURAL PREDICTION AND ANTIGENIC ANALYSIS OF A HYPOTHETICAL PLASMODIUM FALCIPARUM PROTEIN USING BIOINFORMATICS TOOLS - Amlabu, Emmanuel; Collins, M. O.; Omale, J.; Adepoju, O. A.; Omeiza, A. S.; Christian, A. N.; Osiekafore, A. A.; Idih, F. M.; Tijani, M.; Akoji, T. F.; Tolulope, V. O.; Adegoke, A. J.; et al. (FUDMA JOURNAL OF SCIENCES, 2024)
Malaria is caused by Plasmodium falciparum which remains a major global health problem and there is no effective vaccine with broad operational impact. The genome of P. falciparum has been sequenced by others indicating 5,600 genes in the genome. Presently, about 60 % of the genes encoding proteins in the parasite have no-known function. Thus, identifying potential drug/vaccine candidates and biomarkers for evaluating malaria transmission intensity such as the uncharacterized protein Q8IJ58 is a crucial step towards effective malaria intervention. Computer-based approach was used to analyze an uncharacterized Plasmodium falciparum protein - Q8IJ58 (Gene ID: PF10_0342, PlasmoDB ID: PF3D7_1035100), for its basic and theoretical information such as the physicochemical properties, probable B- and T- cell epitopes, secondary and tertiary structures, cellular localization, and other criteria important for further in vivo study, for an efficacious vaccine candidate against malaria. The evaluation of the antigenicity and allergenicity showed that this protein was immunogenic and non-allergenic, also, several potential B- and T-cell epitopes were detected. A total of 60 potential post-translational modification sites were found in the sequence, with 56 phosphorylation sites and 4 acylation sites. The secondary structure of Q8IJ58 is made up of 28.34% alpha-helix, 53.83% random coil, and 17.83% extended strand. Iterative Threading ASSEmbly Refinement (I-TASSER) was used for the three-dimensional structure prediction of Q8IJ58, the Ramachandran plot showed that 96.7% residues were in the most favored region, 2.1% in the allowed regions, and 0.2% residues in the allowed regions, with an overall quality factor of 98.47%...